Lexical decision with pseudohomophones and reading in the semantic variant of primary progressive aphasia: A double dissociation. (June 2016) - Boukadi, Mariem; Potvin, Karel; Macoir, Joël; Jr. Laforce, Robert; Poulin, Stéphane; Brambati, Simona M.; Wilson, Maximiliano A.
Abstract: The co-occurrence of semantic impairment and surface dyslexia in the semantic variant of primary progressive aphasia (svPPA) has often been taken as supporting evidence for the central role of semantics in visual word processing. According to connectionist models, semantic access is needed to accurately read irregular words. They also postulate that reliance on semantics is necessary to perform the lexical decision task under certain circumstances (for example, when the stimulus list comprises pseudohomophones). In the present study, we report two svPPA cases: M.F. who presented with surface dyslexia but performed accurately on the lexical decision task with pseudohomophones, and R.L. who showed no surface dyslexia but performed below the normal range on the lexical decision task with pseudohomophones. This double dissociation between reading and lexical decision with pseudohomophones is in line with the dual-route cascaded (DRC) model of reading. According to this model, impairments in visual word processing in svPPA are not necessarily associated with the semantic deficits characterizing this disease. Our findings also call into question the central role given to semantics in visual word processing within the connectionist account. Highlights: Reading and lexical decision (LD) deficits were investigated in two svPPA cases. The reading task included irregular words; the LD task included pseudohomophones. The case MF had surface dyslexia but no impairment in LD with pseudohomophones. The case RL had no surface dyslexia but impairment in LD with pseudohomophones. Reading and LD impairments in svPPA may not be directly caused by semantic damage.